Peritonitis in Latin America - Barretti, Pasqual; Bastos, Kleyton A.; Dominguez, Jorge; Caramori, Jacqueline C.T. (Multimed Inc, 2007)
Peritoneal dialysis has a high acceptance rate in Latin America, thus the knowledge concerning complication patterns is of great relevance. This work reviews Latin American data on peritonitis, the most serious complication of peritoneal dialysis. The incidence of peritonitis has been reduced over time, concomitantly with the incorporation of safer exchange systems and the use of prophylactic measurements. Today, rates lower than 1 episode per 24 patient-months are commonly reported. Furthermore, changes in causative organisms have been observed, with predominance of Staphylococcus aureus up through the mid-1990s, as well as increases in coagulase-negative staphylococcus and participation of gram negatives. However, the prevalence of S. aureus is still high, due possibly to climatic conditions and the elevated prevalence of carriers. Resolution rate varies from 55% to 78%, transfer to hemodialysis from 10.9% to 15.4%, and death in 3% to 9.9% of cases. Outcome is worse in S. aureus episodes compared to those with coagulase-negative staphylococcus, despite the higher percentage of oxacillin-resistant strains among the former. In general, despite socioeconomic or climatic conditions, our results are similar to those in developed countries, perhaps as a consequence of technological improvements and/or center expertise. Copyright © 2007 International Society for Peritoneal Dialysis.
Keywords: Latin America; Peritonitis